Urethral multiplicity in boys: systematic review of case reports and case series from the last 15 years - Gozar, Horea; Bara, Zsolt; Kovacs, Evelyn; Gozar, Iulia; Derzsi, Zoltan (Frontiers in Pediatrics, 2024)
Introduction: Urethral multiplicity is a rare congenital anomaly characterized by the presence of two or more urethral channels. It is more common in males and can cause double urinary stream, incontinence, obstruction, and recurrent urinary infections. Diagnosis is difficult due to diverse clinical manifestations. Implementing an evidence-based treatment plan is challenging due to the need for more concise and informative summary publications. Our paper provides a comprehensive review of the management of this pathology and might serve as a valuable resource for pediatric urologists and specialists in the field.Methods: A comprehensive search in four electronic databases, PubMed®, PubMed Central® (PMC), Scopus, and Clarivate Analytics's Web of Science (WoS), was conducted to identify case reports and series published between 2008 and 2023 on urethral multiplicities. The quality of the articles was assessed using qualified instruments. Covidence® tool-guided synthesis was followed by individual patient data extraction. Further classifications and analysis were made using Microsoft Excel®.Results: Out of the 90 papers included in the review, 62 were case presentations, and 28 were case series. We found 250 boys with urethral multiplicity. Based on Effman's classification, there were 38 cases of type I (15.3%), 21 type IIA1 (8.4%), 55 type IIA2 (22.1%), 91 type IIA2Y (36.5%), 4 type IIB (1.6%), and 6 type III (2.4%) urethral duplications. There were 19 cases of prepubic sinuses (7.6%), 9 triplications (3.6%), and 6 unknown forms (2.4%). We have provided data for each type, including clinical presentation, investigations, surgical management, and outcomes.Conclusions. Urethral multiplicities are a rare and varied group of malformations that require highquality imaging examination for successful management. Treatment is specific to each patient and may depend on the surgeon's preference or skill.